The Impact of Polymerization Technique and Glass-Fiber Reinforcement on the Flexural Properties of Denture Base Resin Material - Al-Thobity, Ahmad M. (European Journal of Dentistry, 2020)
Objective Different polymerization and reinforcement techniques have been tested to enhance the mechanical characteristics of denture base acrylic resins. The goal of the present study was to evaluate the influence of autoclave polymerization techniques with glass fiber reinforcement on the flexural strength and elastic modulus of polymethyl methacrylate denture base resins.Materials and Methods Ninety specimens were fabricated from heat-polymerized acrylic resin and randomly distributed depending on the polymerization technique into three groups (n = 30): water bath polymerization, short-cycle autoclave polymerization, and long-cycle autoclave polymerization. Each group was further divided into three subgroups (n = 10) based on the concentration of glass fiber 0, 2.5, and 5wt%. The flexural strength and elastic modulus were investigated using a universal testing machine. One-way ANOVA and Tukey’s post hoc test were performed to analyze the results (α = 0.05).Results The flexural strength and elastic modulus values were significantly higher in 5wt% glass fiber reinforced long-cycle autoclave group in comparison with the other test groups (p < 0.05).Conclusions The long-cycle autoclave polymerization technique with the glass fiber reinforcement significantly increased the flexural strength and elastic modulus of the denture base resin material.
Keywords: autoclave; water bath; polymerization; glass fiber; denture base